Nrf2 is activated by disruption of mitochondrial thiol homeostasis but not by enhanced mitochondrial superoxide production - Cvetko, Filip (J Biol Chem, 2020)
The transcription factor nuclear factor erythroid 2–related factor 2 (Nrf2) regulates the expression of genes involved in antioxidant defenses to modulate fundamental cellular processes such as mitochondrial function and GSH metabolism. Previous reports proposed that mitochondrial reactive oxygen species production and disruption of the GSH pool activate the Nrf2 pathway, suggesting that Nrf2 senses mitochondrial redox signals and/or oxidative damage and signals to the nucleus to respond appropriately. However, until now, it has not been possible to disentangle the overlapping effects of mitochondrial superoxide/hydrogen peroxide production as a redox signal from changes to mitochondrial thiol homeostasis on Nrf2. Recently, we developed mitochondria-targeted reagents that can independently induce mitochondrial superoxide and hydrogen peroxide production mitoParaquat (MitoPQ) or selectively disrupt mitochondrial thiol homeostasis MitoChlorodinitrobenzoic acid (MitoCDNB). Using these reagents, here we have determined how enhanced generation of mitochondrial superoxide and hydrogen peroxide or disruption of mitochondrial thiol homeostasis affects activation of the Nrf2 system in cells, which was assessed by the Nrf2 protein level, nuclear translocation, and expression of its target genes. We found that selective disruption of the mitochondrial GSH pool and inhibition of its thioredoxin system by MitoCDNB led to Nrf2 activation, whereas using MitoPQ to enhance the production of mitochondrial superoxide and hydrogen peroxide alone did not. We further showed that Nrf2 activation by MitoCDNB requires cysteine sensors of Kelch-like ECH-associated protein 1 (Keap1). These findings provide important information on how disruption to mitochondrial redox homeostasis is sensed in the cytoplasm and signaled to the nucleus.